Artes da Memória: ficcionalização da matéria biográfica e representações do intelectual, em Graciliano Ramos e Guimarães Rosa - Lima, Deise Dantas (2006)
The present work ana lyses - mainly. in Graciliano Ramos Infância and in Guimarães Rosa s Campo Geral narrative strategies employed to ficcionalize biographycal subjects. It also examines the procedures that contribute to subvert memorialistic tradition and to build new representations of the intellectual